From Exclusion to Empowerment: Redesigning E-Learning to Mitigate Risks for Disabled Students - Rauf, Ummu Ajirah Abdul; Deli, Mazzlida Mat; Husin, Nanang (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study explores how e-learning platforms can be redesigned to empower disabled students by mitigating their educational risks, such as accessibility barriers, communication challenges, and unequal participation. Using a qualitative approach, the research combines literature reviews, case studies, and user feedback to analyze current e-learning environments. It evaluates how AI technologies like ChatGPT can facilitate content accessibility, improve interaction, and support personalized learning experiences for disabled students. This study identifies key risks: limited content adaptability, poor user interface design, and social isolation, which hinder disabled students' academic engagement. It proposes a framework integrating assistive AI tools to transform these platforms into inclusive, low-risk learning environments. Results indicate that AI-driven adaptations can enhance content comprehension, foster collaboration, and improve learning outcomes for disabled students. This study focuses on higher education contexts and may require further validation across diverse educational levels and technological infrastructures. Additionally, reliance on evolving AI technology presents challenges related to affordability and accessibility. This study contributes to the growing field of inclusive education by offering a novel, AI-supported framework to redesign e-learning platforms. It addresses the gap between technological advancement and practical accessibility solutions, emphasizing risk mitigation for disabled students. The findings provide valuable insights for educators, policymakers, and technology developers aiming to create equitable, empowering learning experiences for all learners.